EFEKTIVITAS PENGGUNAAN CELEBRITY DIPLOMACY BTS (BANGTAN SONYEONDAN) SEBAGAI GOODWILL AMBASSADOR UNICEF DALAM MELAKUKAN KAMPANYE ANTI-KEKERASAN “LOVE MYSELF” - Eny Wahyuni; Lalu Puttrawandi Karjaya; Valencia Husni (The Department of International Relations Universitas Mataram, 2023)
Violence against children is a big problem that still often occurs in all parts of the world, both online violence (cyberbullying) and violence that occurs in person. One of UNICEF’s efforts to solve the issue is by initiating celebrity diplomats, namely BTS, to cooperate with UNICEF in the anti-violence Campaign against children